2010
DOI: 10.1007/s00705-010-0787-9
|View full text |Cite
|
Sign up to set email alerts
|

The HPV-16 E7 oncoprotein is expressed mainly from the unspliced E6/E7 transcript in cervical carcinoma C33-A cells

Abstract: The HPV-16 E6/E7 early transcripts are first produced as bicistronic or polycistronic mRNAs, and about 90% of the original pre-mRNA is spliced to produce three new alternative mRNAs. HPV-16 spliced transcripts are expressed heterogeneously in tumors and cell lines. Our results suggest that suboptimal splicing acceptor sites in E6/E7 intron 1 and the differential expression of splicing factors are involved in the production of the heterogeneous splicing profile in cell lines. The unspliced pre-mRNA and the alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Whether splicing of E6 enhances the translation efficiency of E7 is still controversial. Whereas in some studies an increase in the efficiency of E7 translation was reported (25)(26)(27), in other studies, E7 is translated equally efficiently from spliced and unspliced transcripts (28,29). Nevertheless, E6* has been found to function independently of E6 in the transformation process (30,31).…”
mentioning
confidence: 95%
“…Whether splicing of E6 enhances the translation efficiency of E7 is still controversial. Whereas in some studies an increase in the efficiency of E7 translation was reported (25)(26)(27), in other studies, E7 is translated equally efficiently from spliced and unspliced transcripts (28,29). Nevertheless, E6* has been found to function independently of E6 in the transformation process (30,31).…”
mentioning
confidence: 95%
“…References are represented by superscript lowercase letters, where a refers to the detected mixed A and B spliceosomal complexes in Bennett et al [60]; b is that detected in B complexes in Deckert et a l. [34]; c, detected in A, B, or C complexes in Herold et al [59]; d, detected in A, B, or C complexes in Agafonov et al [35]; e, detected in C complexes in Jurica et al [17]; f, detected in C complexes in Yang et al [54]; g, detected in mixed complexes in Zhou et al [38]; h, Rasche et al [61]; i, detected supra-spliceosomal (SS) complexes isolated in bulk in Chen et al [33]; and j, detected in Behzadnia et al [52]; spliceosomal complex = sp1 complex. transcripts are heterogeneously expressed in tumor cells, but the cause of the heterogeneity is poorly understood [21,22]. Recognition of the In-1 splicing sequences is probably affected by the availability of a set of splicing factors, which are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The HPV-16 E6/E7 pre-mRNA is alternatively spliced and produces 4 transcripts. One of them is the unspliced pre-mRNA self, which is the most important of these mRNAs, since it is the only source of the full length E6 oncoprotein [21,25]. In-1 is constituted by one donor site and three acceptor sites, but only the first two acceptors are located in the E6 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations